Effects of ball milling on Structure and Electrochemical Properties of Na4MnV(PO4)3. Issue 1 (1st October 2022) - Tang, Ao; Yang, Chenguang; Hu, Pu
Abstract : Na4 MnV(PO4 )3 is regarded as a promising candidate as cathode material for Na-ion batteries (SIB) due to its low cost and high energy density. However, it suffers from fast capacity decay upon cycles, hindering its further commercialization. The ball milling technology was adopted in this study to control the particle size of Na4 MnV(PO4 )3, and the correlation of electrochemical properties was investigated. With increasing ball milling time, particle size was greatly reduced. The material with 20 minutes of ball milling displayed the best cycling stability and rate capability. It delivered a reversible capacity of 77.1 mAh/g at 0.5 C after 80 cycles, much higher than that of pristine Na4 MnV(PO4 )3 . The decreased particle size might be to blame for the enhanced electrochemical performance, which effectively increased the interfacial contact with the electrolyte and greatly reduced the length of Na-ion diffusion in active particles.